Exploring connections between open quantum systems, relativity and complex quantum networks - Sokolov, Boris (fi=Turun yliopisto|en=University of Turku|, 2020)
This thesis is a collection of works focusing on interrelations between the fields of special relativity, open quantum systems and complex networks. As each of the aforementioned fields encompasses a huge variety of topics, the thesis contains a selection of particular connections. The first half of the thesis considers an open quantum systems approach to the description of relativistic phenomena. As the aforementioned phenomena often involve dynamically evolving counterparts, some non-Markovian aspects of open quantum systems are initially explored. Conditions for complete positivity are derived for a type of phase-covariant time-local master equation and then applied to a non-Markovian master equation with heuristically-derived decay rates. This is relevant in cases when the physicality of the master equation cannot be postulated. The first relativistic system considered is a superposition of coherent states in a gravitational gradient. It is shown to exhibit decoherence induced by gravitational time dilation through interaction between inner degrees of freedom and the centre of mass of the superposition. The decoherence is quantified using various, widely-used non-classicality measures. The decoherence rates are then compared to decoherence induced by classical noise to roughly evaluate the experimental precision necessary to detect gravitationally induced decoherence. In the second relativistic system, the Unruh effect is modeled as an open system where an Unruh-deWitt detector is interacting with bosonic fields. A master equation with time-dependent decay rates for the open system is derived by assuming a non-conventional spacetime path profile for the detector. A particular parameter governing the physical evolution is identified. The system is shown to exhibit non-Markovianity within the completely positive domain of the master equation, the latter ensured by the conditions derived before. The second half of the thesis starts with a definition of complex networks, which are yet not a commonly used tool in quantum physics. The concept of pairwise tomography networks is then introduced as a way to represent many-body quantum states. As the number of pairwise connections grows quadratically with the number of nodes, an efficiently scaling measurement scheme to recover the pairwise tomography networks is presented. The scheme and the concept of pairwise tomography networks are demonstrated to be useful in various applications and the results of a proof-of-principle experiment are shown. One application explored is a paradigmatic spin chain model known as the XX model. A pairwise entanglement network representation of the XX model is shown to suggest new phenomena such as gradual establishment of quasi-long range order accompanied by a symmetry regarding single-spin concurrence distributions. The existence of structural classes and a cyclic self-similarity in the state are revealed.

Tämä väitöskirja on erikoisen suhteellisuusteorian, avoimien kvanttisysteemien ja kompleksisten verkkojen alojen läpileikkauksiin keskittyvä kokoelma. Sillä jokainen edellämainituista aloista sisältää valtavan moninaisuuden erilaisia käsitteitä, väitöskirjaan sisältyy valikoima tietynlaisia yhteyksiä. Väitöskirjan ensimmäinen puolisko käsittelee avoimien kvanttisysteemien lähestymistapaa relativististen ilmiöiden kuvaamiseen. Edellä mainitut ilmiöt yleensä sisältävät dynaamisesti kehittyviä osia, joten tutkitaan avoimien kvanttisysteemien ei-markovisia näkökulmia. Täyspositiivisuuden ehdot johdetaan tietyntyyppiselle faasi-kovariantille ajassa lokaalille master-yhtälölle. Nämä ehdot sovitellaan ei-markoviselle master-yhtälölle jossa on heuristisesti johdetut hajoamisnopeudet. Tämä on merkityksellistä silloin kun master-yhtälön fysikaalisuus ei ole postuloitavissa. Ensimmäinen tarkasteltu relativistinen systeemi on koherenttien tilojen superpositio gravitationaalisessa gradientissa. Sen osoitetaan ilmentävän gravitaationaalisen aikadilataation aiheuttamaa dekoherenssiä sisäisten vapausasteiden ja massakeskipisteen välisten vuorovaikutusten kautta. Tämä dekoherenssi kvantifioidaan käyttämällä useilla laajassa käytössä olevilla ei-klassisuusmitoilla. Dekoherenssinopeuksia verrataan klassisen melun aiheuttamaan dekoherenssiin alustavan gravitaation indusoiman dekoherenssin kokeelliseen havaintoon tarvittavan mittaustarkkuusarvion tekemiseksi. Toisessa tarkasteltavassa relativistisessa systeemissä, Unruhin ilmiö mallinnetaan avoimena kvanttisysteeminä jossa Unruh-deWitt detektori vuorovaikuttaa bosonikenttien kanssa. Olettamalla detektorille epätavanomainen aika-avaruuspolkuprofiili johdetaan avoimelle kvanttisysteemille master-yhtälö ajasta riippuvin hajoamisnopeuksin. Tunnistetaan erityinen fyysista evoluutiota hallitseva parametri. Systeemin näytetään omaavan ei-markovisuutta master-yhtälön täyspositiivisilla alueilla, täyspositiivisuus taataan aiemmin johdetulla tavalla Väitöskirjan toisen puoliskon alussa määritellään kompleksiset kvantti-verkot, jotka eivät vielä ole laajasti käytettyjä työkaluja kvanttifysiikassa. Esitellään uusi tapa esittää monikappalekvanttitiloja parittaisina tomografiaverkkoina. Parittaisten yhteyksien lukumäärän ollessa neliöllisesti verrannollinen solmupisteiden lukumäärään, esitetään tehokkaasti skaalautuva parittaisia tomografiaverkkoja muodostava mittausskeema. Skeema ja parittaisten tomografiaverkkojen konsepti osoitetaan hyödyllisiksi erilaisissa sovelluksissa ja esitetään periaatetodistuskokeen tulokset. Eräänä sovelluksena esitetään XX mallina tunnettu paradigmaattinen spinketjumalli. XX mallin parittaisen kietoutumisen verkkoesityksen näytetään tuovan ilmi uusia ilmiöitä kuten vaiheittaisen kvasipitkän etäisyyden järjestyksen yksittäisten spinien konkurrenssidistribuutioiden symmetrialla. Paljastetaan tilan rakenteellisten luokkien ja syklisten itse-samankaltaisuuksien olemassaolo.